Calidolipeurus, new genus for Lipeurus megalops Piaget, 1880 (Phthiraptera: Ischnocera: Oxylipeurus-complex), with a redescription of the type species and a preliminary key to the Oxylipeurus-complex - Gustafsson, Daniel R.; Lei, Lujia; Zou, Fasheng (European Journal of Taxonomy, 2020)
The chewing louse species Lipeurus megalops Piaget, 1880, is redescribed and illustrated. This species has previously been placed in the genus Oxylipeurus Mjöberg, 1910, but marked differences in preantennal structure, male and female genitalia, abdominal chaetotaxy, and structure of abdominal plates indicate that this species is not closely related to other species in this genus. We therefore erect a new genus, Calidolipeurus gen. nov. for this species. Calidolipeurus is presently monotypic, containing only Calidolipeurus megalops gen. et comb. nov. We also provide a preliminary key to the Oxylipeurus-complex.